Freies Ermessen Dalam Tindakan Nyata di Pemerintah Daerah - Mohamad Fasyehhudin (Jurnal Ius Constituendum, 2023)
This study aims to examine the authority of regional government agencies/officials in implementing Freies Ermessen in regional policies and the binding power of Freies Ermessen as legal provisions in the regions. The novelty of this research is to analyze the application of Freies Ermessen in regional policies. This study uses a normative juridical approach. The results of this study are the use of Freies Ermessen Government Officials to expedite government administration, fill legal voids, provide legal certainty, overcome government stagnation in certain circumstances for the benefit and public interest. In implementing the Freies Ermessen Decree as a legal policy in the region, UUAP government agencies/officials are prohibited from abusing authority, which includes prohibitions on exceeding authority, mixing authority and not acting arbitrarily so that discretionary policies have binding power as legal decisions.  Penelitian ini bertujuan untuk mengkaji mengenai kewenangan badan/pejabat pemerintahan daerah dalam penerapan Freies Ermessen dalam kebijakan di daerah serta kekuatan mengikat Freies Ermessen sebagai ketetapan hukum di daerah. Kebaharuan penelitian ini adalah untuk menganalisis penerapan Freies Ermessen dalam kebijakan di daerah. Penelitian ini menggunakan pendekatan yuridis normatif. Hasil penelitian ini adalah penggunaan Freies Ermessen Pejabat Pemerintahan diterapkan untuk melancarkan penyelenggaraan pemerintahan, mengisi kekosongan hukum, memberikan kepastian hukum, mengatasi stagnasi pemerintahan dalam keadaan tertentu guna kemanfaatan dan kepentingan umum. Dalam melaksanakan Keputusan Freies Ermessen sebagai kebijakan hukum di daerah, badan/pejabat pemerintahan UUAP dilarang menyalahgunakan wewenang, yang meliputi larangan melampaui wewenang, mencampuradukan wewenang dan dilarang bertindak sewenang-wenang agar kebijakan diskresi memiliki kekuatan mengikat sebagai keputusan hukum